7.0k views
14 votes
Find the inverse of the function

Find the inverse of the function-example-1
User Lapo
by
5.0k points

1 Answer

9 votes

as you already know, to get the inverse of any expression we start off by doing a quick switcheroo on the variables and then solving for "y", let's do so.


\stackrel{h(x)}{y}~~ = ~~6\sqrt[3]{2x+5}-1\implies \stackrel{\textit{quick switcheroo}}{x~~ = ~~6\sqrt[3]{2y+5}-1} \\\\\\ x+1=6\sqrt[3]{2y+5}\implies \cfrac{x+1}{6}=\sqrt[3]{2y+5}\implies \left( \cfrac{x+1}{6} \right)^3=\left( \sqrt[3]{2y+5} \right)^3


\left( \cfrac{x+1}{6} \right)^3=2y+5\implies \left( \cfrac{x+1}{6} \right)^3-5=2y\implies \cfrac{\left( (x+1)/(6) \right)^3-5}{2}=y \\\\\\ \cfrac{\left( (x+1)/(6) \right)^3}{2}-\cfrac{5}{2}=y\implies \cfrac{~~ ((x+1)^3)/(6^3)~~}{2}-\cfrac{5}{2}=y\implies \cfrac{(x+1)^3}{432}-\cfrac{5}{2}=\stackrel{y}{h^(-1)(x)}

User Anjanesh
by
5.5k points